2020
DOI: 10.3390/ijms21072289
|View full text |Cite
|
Sign up to set email alerts
|

Musashi-1: An Example of How Polyalanine Tracts Contribute to Self-Association in the Intrinsically Disordered Regions of RNA-Binding Proteins

Abstract: RNA-binding proteins (RBPs) have intrinsically disordered regions (IDRs) whose biophysical properties have yet to be explored to the same extent as those of the folded RNA interacting domains. These IDRs are essential to the formation of biomolecular condensates, such as stress and RNA granules, but dysregulated assembly can be pathological. Because of their structural heterogeneity, IDRs are best studied by NMR spectroscopy. In this study, we used NMR spectroscopy to investigate the structural propensity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 67 publications
(95 reference statements)
2
12
0
Order By: Relevance
“…Although present in different regions, Msi1 binding sites are preferentially located at 3’ UTRs, agreeing with its described roles in translation regulation and mRNA stability. Additional Msi1 functions have been recently described that include its participation in stress granules and the formation of tau aggregates [ 67 , 68 ]. Targets of Musashi proteins have been identified in many different cell types by CLIP and RIP and encompass a variety of cancer-related processes and pathways [ 12 , 25 , 37 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although present in different regions, Msi1 binding sites are preferentially located at 3’ UTRs, agreeing with its described roles in translation regulation and mRNA stability. Additional Msi1 functions have been recently described that include its participation in stress granules and the formation of tau aggregates [ 67 , 68 ]. Targets of Musashi proteins have been identified in many different cell types by CLIP and RIP and encompass a variety of cancer-related processes and pathways [ 12 , 25 , 37 , 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were purified using the same protocol, which has been described in detail elsewhere (Chen and Huang 2020). In short, transformed E. coli BL21(DE3) cells were grown at 37 °C until the O.D.…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
“…The Msi-1C construct in this study (residues number 237 to 362) was cloned from a previous longer construct (Chen and Huang 2020). We removed a strongly hydrophobic region reported to contain binding sites for PABP and GLD2 (Fox, et al 2015), which is irrelevant to the present study and whose removal improves the protein's solubility.…”
Section: Dna Constructsmentioning
confidence: 99%
“…Of note, Msi proteins have also been associated with neurodegenerative diseases. Msi proteins have intrinsically disordered regions that could lead to their aggregation and interaction with Tau (Chen and Huang, 2020 ; Montalbano et al, 2020 ), and Msi1/2 were found to form oligomers in brains of patients with Alzheimer's disease, amyotrophic lateral sclerosis, and frontotemporal dementia (Sengupta et al, 2018 ; Montalbano et al, 2020 ).…”
Section: The Musashi Rna Binding Protein Family As Master Regulators Of Neuronal Developmentmentioning
confidence: 99%